Pertumbuhan dan hasil jamur merang (volvariella volvacea) pada berbagai media tanam limbah pertanian - Sukmawati, Sukmawati; J, Aisah; Mulyadi, Mulyadi (Jurnal Agrotek Ummat, 2024)
Straw mushrooms are a food ingredient that is much sought after by the public because they have a delicious taste and are beneficial for health with a complete nutritional co mposition consisting of carbohydrates (8.7%); protein (26.49%); fat (0.67%); calcium (0.75%); phosphorus (30%); potassium (44.2%) vitamins and minerals. For the growth of straw mushrooms, they need nutrients which can be fulfilled by the planting medium which can come from agricultural waste. This research aims to determine the growth and yield of straw mushrooms on various types of agricultural waste growing media. This research was designed using a Completely Randomized Design (CRD) with 4 treatment levels, namely: P0 = 50 kg rice straw, P1 = 50 kg reeds, P2 = 50 kg corn cobs, P3 = 50 kg sugarcane bagasse. The research was repeated 4 times to obtain 16 treatments. The results of the study showed that the effect of significant differences in treatment was only found in the observation parameter of the number of fruiting bodies of straw mushrooms, while the other parameters did not show significant differences. The results of the observations showed that the planting media treatment with rice straw gave the best results with a fruit body number of 63.5 fruit bodies, a fruit body diameter of 3.05 cm, a fruit body height of 4.42 cm and a fruit body wet weight of 898 gr. The time for pinheads to appear on rice straw planting media is faster than other planting media